Kewirausahaan Produk Lilin Aromaterapi Anti Nyamuk dan Ramah Lingkungan bagi Mahasiswa dan UMKM di Kalurahan Banyuraden, Gamping, Sleman - Heru Subaris Kasjono; Nunik Andina Rahmawati; Fadelia Sabrina Putri Cantika; Tri Wahyuni Kusuma Anggun; Asmaul Jannah; Sarifah Syadiyah; Bambang Supriyanta; Romeo Annur Putra (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Waste cooking oil that is disposed of without treatment can cause environmental pollution and endanger human health if continuously ignored. One innovative solution with economic value to address this problem is by producing mosquito-repellent aromatherapy candles. This activity, titled “LAMITA,” was carried out through entrepreneurship training and socialization provided to students and MSMEs (Micro, Small, and Medium Enterprises) in Banyumuncar, Banyuraden Village, Gamping, Sleman, Special Region of Yogyakarta. The training introduced techniques for processing unused cooking oil into eco-friendly mosquito-repellent aromatherapy candles, while also developing participants’ entrepreneurial skills. Students and MSME actors were guided step by step, starting from oil purification, mixing natural essential oils, to candle molding and packaging. The purpose of this activity was not only to promote environmental awareness but also to encourage creativity and innovation in producing high-value products from waste materials. The results showed that participants gained increased knowledge and skills in entrepreneurship, as well as awareness of the importance of managing waste responsibly. This activity highlights that entrepreneurship training combined with environmental sustainability can empower communities to generate economic benefits while contributing to health and ecological protection.